Pequeños sujetos en formación: la construcción de la identidad en las películas infantiles - Abud Jaso, Juan José (Theoría. Revista del Colegio de Filosofía, 2015)
In this paper I will examine the relationship between the theory of ideology of Althusser and Zizek, mainly, and film aimed at children and adolescents. I believe that children’s film is a way of questioning individuals so that they are functional and tame towards the capitalist system of exploitation. My thesis is that the film industry generally constructs subjective positions defined by ideology, that is, the social matrix that makes us speak and act according to the different roles we are assigned by the society in which we live. Thus, children’s films, in particular, provides us with a well-defined field and we can account through it how ideological interpellation works and how subjects that libidinally support the dominant system are manufactured.